The air resistance of racing cyclists - Nonweiler, T. (College of Aeronautics, Cranfield, 1956)
Tests in the closed-section wind-tunnel on three different cyclists mounted on a racing bicycle are described, and figures quoted for the recorded air resistance. Some comments are also included on the implications of the results concerning the power-output of racing cyclists.